Dianne Rayson, Bonhoeffer and Climate Change: Theology and Ethics for the Anthropocene - Mayes, Eve (Journal for the Academic Study of Religion, 2022)
Dianne Rayson, Bonhoeffer and Climate Change: Theology and Ethics for the Anthropocene. London: Rowman and Littlefield, 2021, pp. 283, ISBN: 978-1-9787-0183-0 (hbk). US110.